PENERAPAN TEKNIK MOLEKULAR GASTRONOMI PADA KOMBINASI BENTUK KUE PUTU MAYANG - Farham Fairus Kamal; Herra Herryani (Eduturisma, 2020)
The background of this research was because the writer wanted to changes the technique and appearance of putu Mayang cakes to make them more interesting to look at and also make consumers have a different experience eating putu Mayang cakes. Namely how to process with molecular gastronomy, if usually putu Mayang cake is processed by steaming, with this technique it doesn't need to go through the steaming process and for its presentation is slightly different from the usual putu Mayang cake. From the research that has been done, The use of Molecular Gastronomy techniques in cake putu Mayang in terms of processing which shortens the time and is more practical. Putu Mayang cake if processed with gelification technique will have a more attractive appearance compared to cake traditional putu Mayang and consumers will experience a different eating experience than usual. In terms of the ingredients used are almost the same as what is used on cake traditional putu Mayang only removes rice flour and tapioca replaced by jelly and carrageenan.